Conserved and differential transcriptional responses of peroxisome associated pathways to drought, dehydration and ABA. (19th July 2018) - Ebeed, Heba T; Stevenson, Sean R; Cuming, Andrew C; Baker, Alison
Abstract : Peroxisome biogenesis, peroxisome β-oxidation and antioxidant enzymes show conserved upregulation in response to ABA and water deficit-inducing treatments, highlighting an overlooked role for peroxisomes in response to drought. Abstract: Plant peroxisomes are important components of cellular antioxidant networks, dealing with ROS generated by multiple metabolic pathways. Peroxisomes respond to environmental and cellular conditions by changing their size, number, and proteomic content. To investigate the role of peroxisomes in response to drought, dehydration and ABA treatment we took an evolutionary and comparative genomics approach. Colonisation of land required evolution of dehydration tolerance in the absence of subsequent anatomical adaptations. Therefore, the model bryophyte Physcomitrella patens, the model dicot Arabidopsis thaliana and wheat ( Tricitcum aestivum ), a globally important cereal crop were compared. Three sets of genes namely ' PTS1 genes' (a proxy for genes encoding peroxisome targeted proteins), PEX genes (involved in peroxisome biogenesis) and genes involved in plant antioxidant networks were identified in all 3 species and their expression compared under drought (dehydration) and ABA treatment. Genes encoding enzymes of β-oxidation and gluconeogenesis, antioxidant enzymes including catalase and glutathione reductase and PEX3 and PEX11 isoforms showed conserved up-regulation, and peroxisome proliferation was induced by ABA in moss. Interestingly, expression of some of these genes differed between drought sensitive and resistant genotypes of wheat in line with measured photosynthetic and biochemical differences. These results point to an underappreciated role for peroxisomes in drought response.